"Do you consider animal welfare to be important?" activating cognitive dissonance via value activation can promote vegetarian choices. (October 2022) - Bouwman, Emily P.; Bolderdijk, Jan Willem; Onwezen, Marleen C.; Taufik, Danny
Abstract: Reducing global meat consumption can improve animal welfare, environmental and health issues. Although many people recognize this, they also continue eating meat. When people become aware of their conflicting cognitions regarding meat consumption, such as finding both animal welfare and eating meat important, it can result in aversive feelings, known as cognitive dissonance. We add to the literature by exploring whether cognitive dissonance can be used to support desired behavioral choices. More specifically, we examine whether activating peoples' pre-existing animal welfare values, by stimulating them to reflect on whether they consider animal welfare to be important, can trigger cognitive dissonance and in turn promote the choice for vegetarian meals. An online study showed that our value activation strategy indeed increased the amount of cognitive dissonance people experience when thinking of consuming meat, which in turn increased their intention to eat a vegetarian meal, especially among those with a strong pro-environmental self-identity. A subsequent field study in a restaurant showed that our value activation strategy (almost) doubled the percentage of vegetarian burgers ordered. Our findings show that stimulating people to reflect on whether they consider animal welfare to be important can force people to face their inner conflict regarding meat consumption and channel that into choosing a vegetarian meal. Highlights: Stimulating people to reflect on whether they consider animal welfare important increases vegetarian choices via dissonance. Meat-related cognitive dissonance has the potential to translate into meat reduction. Meat-related cognitive dissonance can be triggered by the moral value animal welfare, but not by the less moral value health. People with a strong pro-environmental self-identity are more prone to choose a vegetarian meal as a reaction to dissonance.